2006
DOI: 10.1523/jneurosci.0661-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Subtypes of Somatostatin-Containing Neocortical Interneurons Revealed in Transgenic Mice

Abstract: GABA-releasing inhibitory interneurons in the cerebral cortex can be classified by their neurochemical content, firing patterns, or axonal targets, to name the most common criteria, but whether classifications using different criteria converge on the same neuronal subtypes, and how many such subtypes exist, is a matter of much current interest and considerable debate. To address these issues, we generated transgenic mice expressing green fluorescent protein (GFP) under control of the GAD67 promoter. In two of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

57
566
5
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(634 citation statements)
references
References 74 publications
57
566
5
6
Order By: Relevance
“…1C), as Ma et al (2006) also observed for GIN cells. Other cells either did not have an axon projecting to layer I or the axonal destination could not be determined due to inadequate filling or high background staining.…”
Section: Characteristics Of Gin Cellssupporting
confidence: 81%
See 3 more Smart Citations
“…1C), as Ma et al (2006) also observed for GIN cells. Other cells either did not have an axon projecting to layer I or the axonal destination could not be determined due to inadequate filling or high background staining.…”
Section: Characteristics Of Gin Cellssupporting
confidence: 81%
“…Based on the fact that many GIN cells have dense axonal projections to layer I (Halabisky et al 2006;Ma et al 2006; this study), they can generally be categorized morphologically as Martinotti cells, although we did find some GIN cells that did not project to layer I. In addition, these cells share multiple characteristics with other described Martinotti cells, including being somatostatin expressing (Halabisky et al 2006;Ma et al 2006;Oliva Jr et al 2000;Wang et al 2004;Xu et al 2006), receiving facilitating input from pyramidal cells (Silberberg and Markram 2007), and showing spike-rate adaptation (Silberberg and Markram 2007;Wang et al 2004).…”
Section: Identity Of Gin Cellsmentioning
confidence: 64%
See 2 more Smart Citations
“…It is expected that, during the acquisition of a new motor ability, both kinetic commands and kinematic parameters should present an intrinsic homogeneity. Cluster analysis is a powerful tool for the analysis of such data (Taganova and Silakov, 1980;Banfield and Raftery, 1993;Hair et al, 1998;Ma et al, 2006). This algorithm for the processing of physiological recordings provides more homogeneity in the experimental database for the subsequent dynamic correlation analysis.…”
Section: Construction Of a Hierarchical Cluster Tree With Kinetic Neumentioning
confidence: 99%